Combinatorial Effects of the Natural Products Arctigenin, Chlorogenic Acid, and Cinnamaldehyde Commit Oxidation Assassination on Breast Cancer Cells - Caroline Schuster; Nicholas Wolpert; Naima Moustaid-Moussa; Lauren S. Gollahon (MDPI AG, 2022)
Major obstacles in current breast cancer treatment efficacy include the ability of breast cancer cells to develop resistance to chemotherapeutic drugs and the off-target cytotoxicity of these drugs on normal cells, leading to debilitating side effects. One major difference between cancer and normal cells is their metabolism, as cancer cells acquire glycolytic and mitochondrial metabolism alterations throughout tumorigenesis. In this study, we sought to exploit this metabolic difference by investigating alternative breast cancer treatment options based on the application of phytochemicals. Herein, we investigated three phytochemicals, namely cinnamaldehyde (CA), chlorogenic acid (CGA), and arctigenin (Arc), regarding their anti-breast-cancer properties. These phytochemicals were administered alone or in combination to MCF-7, MDA-MB-231, and HCC1419 breast cancer or normal MCF-10A and MCF-12F breast cells. Overall, our results indicated that the combination treatments showed stronger inhibitory effects on breast cancer cells versus single treatments. However, only treatments with CA (35 μM), CGA (250 μg/mL), and the combination of CA + CGA (35 μM + 250 μg/mL) showed no significant cytotoxic effects on normal mammary epithelial cells, suggesting that Arc was the driver of normal cell cytotoxicity in all other treatments. CA + CGA and, to a lesser extent, CGA alone effectively induced breast cancer cell death accompanied by decreases in mitochondrial membrane potential, increased mitochondrial superoxide, reduced mitochondrial and glycolytic ATP production, and led to significant changes in cellular and mitochondrial morphology. Altogether, the combination of CA + CGA was determined as the best anti-breast-cancer treatment strategy due to its strong anti-breast-cancer effects without strong adverse effects on normal mammary epithelial cells. This study provides evidence that targeting the mitochondria may be an effective anticancer treatment, and that using phytochemicals or combinations thereof offers new approaches in treating breast cancer that significantly reduce off-target effects on normal cells.